Impact of Silver and Copper Oxide Nanoparticles on Anaerobic Digestion of Sludge and Bacterial Community Structure - Zainab K. Abdulsada; Richard Kibbee; Juliska Princz; Banu Örmeci (Nanomaterials)
The effect of metal nanoparticles on the anaerobic digestion of sludge and the sludge bacterial community are still not well-understood, and both improvements and inhibitions have been reported. This study investigated the impact of 2, 10, and 30 mg/g TS silver and copper oxide nanoparticles (AgNPs and CuONPs) on the mesophilic anaerobic digestion of sludge and the bacterial community structure. The reactors were monitored for changes in tCOD, sCOD, TS, VS, biogas generation, and cell viability. Also, the relative abundance and taxonomic distribution of the bacterial communities were analyzed at the phylum and genus levels, including the genera involved in anaerobic digestion. Both AgNPs and CuONPs exhibited some inhibition on anaerobic digestion of sludge and biogas generation, and the inhibition was more evident at higher concentrations. CuONPs had a stronger inhibitory effect compared to AgNPs. After the introduction of AgNPs and CuONPs, cell viability initially decreased over the first two weeks but recovered after that. At high concentrations, AgNPs and CuONPs decreased the overall bacterial diversity, and inhibited the dominant bacterial species, allowing those in less abundance to flourish. The relative abundance of the bacteria responsible for hydrolysis and acidogenesis increased and the relative abundance of acetogenic bacteria decreased with higher AgNP and CuONP concentrations. The majority of the parameters measured for monitoring the anaerobic digestion performance and bacterial community were not statistically significant at 2 mg/g TS of AgNPs and CuONPs, which represents naturally present concentrations in wastewater sludge that are below the USEPA ceiling concentration limits.